The Fourth Industrial Revolution – Smart Technology, Artificial Intelligence, Robotics and Algorithms: Industrial Psychologists in Future Workplaces - Oosthuizen, Rudolf M. (Frontiers in Artificial Intelligence, 2022)
STARA (smart technology, artificial intelligence, robotics, and algorithms) is predicted to replace a third of the jobs that exist today. Almost twice as many current work tasks will be handled by robots by 2025 compared to 2019. 133 million new jobs could be created between 2019 and 2022 as a result of rapid changes in machine and algorithm development (World Economic Forum, 2018). Industrial psychologists are playing an increasingly important role in the workplace due to these trends. The objective of this article is to present a critical review of industrial psychologists in future workplaces in the context of the Fourth Industrial Revolution (4IR) (Venturini, 2022). A competence model is posed for industrial psychologists to perform a strategic intelligence role in organisations in the Fourth Industrial Revolution.